2022
DOI: 10.1002/advs.202105226
|View full text |Cite
|
Sign up to set email alerts
|

DEPDC1B Promotes Melanoma Angiogenesis and Metastasis through Sequestration of Ubiquitin Ligase CDC16 to Stabilize Secreted SCUBE3

Abstract: The ability of melanoma to acquire metastasis through the induction of angiogenesis is one of the major causes of skin cancer death. Here, it is found that high transcript levels of DEP domain containing 1B (DEPDC1B) in cutaneous melanomas are significantly associated with a poor prognosis. Tissue microarray analysis indicates that DEPDC1B expression is positively correlated with SOX10 in the different stages of melanoma. Consistently, DEPDC1B is both required and sufficient for melanoma growth, metastasis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Since previous studies have shown that DEPDC1B promotes angiogenesis and metastasis of melanoma by competing with CDC16 to promote SCUBE3 secretion ( 20 ), we investigated whether a similar phenomenon exists in breast cancer. For this, we carried out correlation analysis and found that there is a positive correlation between DEPDC1B and SCUBE3 ( R = 0.062, P = 0.042), on transcription level (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Since previous studies have shown that DEPDC1B promotes angiogenesis and metastasis of melanoma by competing with CDC16 to promote SCUBE3 secretion ( 20 ), we investigated whether a similar phenomenon exists in breast cancer. For this, we carried out correlation analysis and found that there is a positive correlation between DEPDC1B and SCUBE3 ( R = 0.062, P = 0.042), on transcription level (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 97%
“…DEPDC1B plays an important role in a variety of cancers, such as liver cancer ( 16 ), chordoma ( 17 ), pancreatic cancer ( 18 ), and non-small-cell lung cancer ( 19 ). It is worth noting that it was reported that DEPDC1B promotes SCUBE3 secretion through competitive binding with ubiquitin ligase CDC16, thus promoting angiogenesis and metastasis of melanoma ( 20 ). However, it is not clear whether DEPDC1B plays a role in breast cancer by affecting ubiquitin events.…”
Section: Introductionmentioning
confidence: 99%
“…Different E3 ubiquitin ligases involved in the ubiquitination of mutated Lamin A/C were reported previously, such as Smurf2 (smad ubiquitination regulatory factor 2), [26] RNF123 (ring finger protein 123), HECW2 (HECT domain ligase W2) and the F-box protein FBXW10. [27] Our proteomic analysis identified several novel ubiquitination-related proteins binding with mutated Lamin A/C, such as CDC16, [28] RANBP2, [29] OTUD4, [30] PSMD6 [31] and DNAJB1, [32] as potential future medication targets. However, further research is needed to validate our findings.…”
Section: Discussionmentioning
confidence: 98%
“… 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 For instance, DEPDC1B regulates the progression of human chordoma by influencing the ubiquitination of baculovirus apoptosis repeat inhibitor 5 (BIRC5) through the ubiquitin‐binding enzyme E2T (UBE2T); 8 in bladder cancer, DEPDC1B and SHC1 collectively serve as tumor promoters, impacting cell proliferation, apoptosis, and migration; 9 DEPDC1B regulates the development of hepatocellular carcinoma by controlling cell proliferation, apoptosis, the cell cycle, and cell migration. It interacts with CDK1, playing a crucial role in DEPDC1B's regulation of hepatocellular carcinoma progression; 10 inducing EMT through the activation of the Akt/GSK3β/Snail pathway, DEPDC1B promotes migration and invasion of pancreatic ductal adenocarcinoma cells; 14 in prostate cancer, DEPDC1B induces EMT and enhances proliferation and migration through the Rac1‐PAK1 signaling pathway by interacting with Rac1; 11 acting downstream of SOX10, DEPDC1B promotes melanoma angiogenesis and metastasis by isolating the stably secreted SCUBE3 through CDC16; 12 and DEPDC1B promotes invasion and metastasis of non‐small cell lung cancer in a Wnt/β‐catenin‐dependent manner. 17 In conclusion, the aforementioned studies collectively demonstrate the significant role played by DEPDC1B in cancer development through the activation of diverse downstream events.…”
Section: Introductionmentioning
confidence: 99%